Konstelasi Golkar dan Elit dalam Politik Indonesia Pasca Pemerintahan Orde Baru - Sadariah Saragih; Lelita Yunia (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article discusses the constellation of Golkar and its elites after the fall of the New Order administration. The conceptual and theoretical framework used includes party functions and the circulation of political elites. This article uses descriptive qualitative research methods based on primary data sourced from direct interviews with Golkar officials and on secondary data from various documents and publications of research. The results of the study show that at the beginning after the end of the New Order administration, the political elites of Golkar developed a constellation of elites that adopted a democratic and bottom-up and collegial culture, leaving behind the authoritarian practices. However, before and after the 2009 presidential election, with the entry of several businessmen into Golkar, the Golkar political elites carried out transactional practices in building power bases both at the party and government levels. This condition interferes with the recruitment processes and puts Golkar in an awkward position when not in power